Development Of Problem Based Learning Student Worksheet on Chemical Bonding Materials - Febriana, Baiq Anita; Masitah, Siti; Satriawan, M Agus (Lembaga Riset Mutiara Akbar, 2024)
The development of science and technology requires humans to remain active and dynamic in facing various changes, including in the field of education. One of the effective learning approaches in developing critical thinking and problem-solving skills is Problem-Based Learning (PBL). In chemistry learning, especially in abstract chemical bonding materials, teaching materials that are able to support the optimal application of PBL are needed. This research aims to develop a PBL-based Student Worksheet (LKPD) on chemical bonding materials that are valid and suitable for use in learning. The results of the validity test show that the LKPD developed has an average validity value of 0.84, which is included in the very high category. In addition, students' responses to the use of PBL-based LKPD reached an average of 78.27%, which was categorized as good, so that this LKPD can be applied effectively in learning.